Green's function, finite elements and microwave planar circuits - Helszajn, J. (Joseph) (John Wiley & Sons, 1996)
The application of Greens function to planar microwave circuits is now very well accepted as a fundamental tool in electromagnetic analysis. Combining various modern mathematical techniques this book presents comprehensive and detailed methods for numerically describing practical microwave circuits (with one or more ports). Features include: Applications of Greens function in: planar resonators, gyromagnetic circuits and junction circulators, together with applied examples Detailed explanation of the use of Finite Element Method (FEM) techniques for calculating the solution of planar isotropic and gyromagnetic circuits Specifically written for industrial engineers specialising in the analysis and development of planar circuits and postgraduate researchersA perfect companion text for developing software for the solution of microwave circuits.